2003
DOI: 10.5897/ajb2003.000-1006
|View full text |Cite
|
Sign up to set email alerts
|

Variations in fatty acid proportions during desiccation of Telfairia occidentalis seeds harvested at physiological and agronomic maturity

Abstract: The effect of desiccation on lipid content, fatty acid composition and the antioxidative enzymic capacity was investigated in seeds of Telfairia occidentalis, harvested at physiological and agronomic maturity. Seeds were dried at 5 and 28 o C, environments that induced different drying and metabolic rates. Desiccation of seeds was associated with decreased antioxidative enzymic capacity (of peroxidase and polyphenoloxidase), and thus increased likelihood of free radical attack and decreased viability (germinab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 23 publications
1
21
1
1
Order By: Relevance
“…44 Hence, the seed oil of T occidentalis can be said to be nutritionally adequate. It is, however, worthy of note that, in the present study and that by Nkang et al, 45 no trace of eleostearic acid was found, while Hilditch 46 reported 19% eleostearic acid content.…”
Section: Fatty Acid Composition Of the Seed Oilcontrasting
confidence: 53%
“…44 Hence, the seed oil of T occidentalis can be said to be nutritionally adequate. It is, however, worthy of note that, in the present study and that by Nkang et al, 45 no trace of eleostearic acid was found, while Hilditch 46 reported 19% eleostearic acid content.…”
Section: Fatty Acid Composition Of the Seed Oilcontrasting
confidence: 53%
“…As antioxidants, the flavonoids and vitamins in T. occidentalis extract could maintain sperm morphology, sperm survival and sperm function (Nwanna & Oboh, 2007). The improvement in sperm count could be attributed to antioxidative properties of tannins and vitamin A presence in the leaves (Nkang et al, 2003). According to Sato et al (2004), vitamin A protects the testis against lipid peroxidation, hence, promotes spermatogenesis and improves structural differentiation of epithelial cells of the epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…Fluted pumpkin ( Telfairia occidentalis ) belongs to Cucurbitaceae family; it is a creeping vine grown in the tropics for its edible leaves and seeds (Nkang, Omokaro, Egbe, & Amanke, ). During growth, it spreads on the ground with a very long twisting tendrils and lobed leaves (Okoli & Mgbeogba, ).…”
Section: Introductionmentioning
confidence: 99%